Pengaruh Pengelolaan Kelas dan Motivasi Peserta Didik Terhadap Hasil Belajar di SMA Jaya Negara Makassar - M.A, A.P Jaya Negara; Elpisah, Elpisah; Syarif, Muqtakdir Nurfalaq (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Education is a fundamental instrument in preparing competitive Human Resources (HR) in the era of globalization, as mandated by Law No. 20 of 2003 on National Education System (Sisdiknas). Educational success highly depends on the central role of teachers, particularly in classroom management competence and the ability to stimulate students' learning motivation. This research aims to analyze the influence of classroom management on students' learning motivation at SMA Jaya Negara Makassar, where preliminary findings indicated low student learning motivation. This research employs a quantitative approach with a correlational design. The population consists of 160 students, with a sample of 40 individuals selected using the Simple Random Sampling technique. Data was collected using questionnaire instruments with a Likert Scale to measure Classroom Management and Learning Motivation. Data analysis involved descriptive and inferential statistics (Simple Linear Regression and t-test). Descriptive results indicate that Classroom Management is in the Poor category (average 71), while Learning Motivation is in the Medium category (average 65). Inferential test results show a significant influence between Classroom Management and students' Learning Motivation (P-value 0.001 < 0.05). The conclusion affirms that teachers' skill in managing the classroom is an important predictor in enhancing students' drive to learn. It is recommended to implement a collective increase in teacher competence in classroom management to maximize student motivation and participation.